General principles of law and international investment arbitration - Gattini, Andrea; Tanzi, Attila; Fontanelli, Filippo (Nijhoff international investment law series ;, 2018)
In General Principles of Law in Investment Arbitration, the authors address selected general principles of law, assessing their functions in investment arbitration. The resulting picture is that of a lively source that escapes doctrinal straitjackets and maintains its relevance.--